Exosome Released From Schwann Cells May Be Involved in Microenergy Acoustic Pulse–Associated Cavernous Nerve Regeneration. Issue 9 (12th July 2020) - Peng, Dongyi; Reed-Maldonado, Amanda B.; Zhou, Feng; Tan, Yan; Yuan, Huixing; Banie, Lia; Wang, Guifang; Tang, Yuxin; He, Leye; Lin, Guiting; Lue, Tom F.
Abstract: Background: Neurogenic erectile dysfunction (ED) is often refractory to treatment because of insufficient functional nerve recovery after injury or insult. Noninvasive mechano-biological intervention, such as microenergy acoustic pulse (MAP), low-intensity pulsed ultrasound, and low-intensity extracorporeal shockwave treatment, is an optimal approach to stimulate nerve regeneration. Aim: To establish a new model in vitro to simulate nerve injury in neurogenic ED and to explore the mechanisms of MAP in vitro . Methods: Sprague-Dawley rats were used to isolate Schwann cells (SCs), major pelvic ganglion (MPG), and cavernous nerve with MPG (CN/MPG). SCs were then treated with MAP (0.033 mJ/mm 2, 1 Hz, 100 pulses), and SC exosomes were isolated. The MPG and CN/MPG were treated with MAP (0.033 mJ/mm 2, 1 Hz) at different dosages (25, 50, 100, 200, or 300 pulses) or exosomes derived from MAP-treated SCs in vitro . Outcomes: Neurite growth from the MPG fragments and CN was photographed and measured. Expression of neurotropic factors (brain-derived neurotrophic factor, nerve growth factor, and neurotrophin-3) was checked. Results: Neurite outgrowth from MPG and CN/MPG was enhanced by MAP in a dosage response manner, peaking at 100 pulses. MAP promoted SC proliferation, neurotropic factor (brain-derived neurotrophic factor, nerve growth factor, and neurotrophin-3) expression, and exosome secretion. SC-derived exosomes significantly enhanced neurite outgrowth from MPG in vitro . Clinical Implications: MAP may have utility in the treatment of neurogenic ED by SC-derived exosomes. Strength & Limitations: We confirmed that MAP enhances penile nerve regeneration through exsomes. Limitations of this study include that our study did not explore the exact mechanisms of how MAP increases SC exosome secretion nor whether MAP modulates the content of exosomes. Conclusion: This study revealed that neurite outgrowth from MPG was enhanced by MAP and by SC-derived exosomes which were isolated after MAP treatment. Our findings indicate that one mechanism by which MAP induces nerve regeneration is by stimulation of SCs to secrete exosomes.